Shifting the paradigm: physician-authorized, student-led efforts to provide harm reduction services amidst legislative opposition - Timothy P. McMullen; Mahan Naeim; Carol Newark; Haden Oliphant; Jeffrey Suchard; Faried Banimahd (BMC, 2021)
Abstract Background For over 30 years, syringe services programs (SSPs) have served as an efficacious intervention for the prevention of HIV and Hepatitis C transmission among persons who use drugs. Despite a strong body of evidence for the effectiveness of SSPs as a preventative public health measure, numerous local and state governments in the United States continue to resist the establishment of new SSPs and aggressively pursue the closure of those already in operation. Commentary In Orange County, California, local officials have repeatedly mobilized in opposition of the establishment of syringe access - thereby hindering access to healthcare for thousands of predominantly unhoused individuals. The county was previously served by the Orange County Needle Exchange Program from 2016 until 2018 when a civil suit brought by the Orange County Board of Supervisors resulted in the closure of the program. For more than 2 years, persons who inject drugs in Orange County lacked reliable access to clean syringes, placing them at increased risk for contracting HIV and Hepatitis C. Here, we comment on the ongoing effort to restore syringe access in Orange County. This collaborative physician-directed endeavor has brought together students and community volunteers to provide vital harm reduction services to a remarkably underserved population. Since the reestablishment of syringe access in Orange County by the Harm Reduction Institute, new legal barriers have arisen including the passage of new municipal legislation banning the operation of syringe exchanges. We are well-equipped to overcome these obstacles. This work serves as an affirmation of assertions made by previous authors regarding the unique qualifications of medical & graduate students as effective harm reductionists. Conclusion Harm reduction services are vital to the health and well-being of people who use drugs. The provision of these services should not be impeded by legislative interference by municipal, county, or state governments.